1998
DOI: 10.1023/a:1005903414734
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The introduction of cranial radiotherapy (CRT) has provided efficient control of overt or subclinical meningeosis in acute leukemia. Especially due to the long-term toxicity of CRT, reduction or elimination of radiotherapy appeared mandatory after cure rates of more than 70% had been achieved in acute lymphoblastic leukemia (ALL). Several large clinical trials of the Berlin-Frankfurt-Münster (BFM) Study Group with more than 3500 patients since 1981 have demonstrated that intensive systemic and intrathecal chem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Patients were administered a modified Berlin-Frankfurt-M ünster 90 (BFM-90) protocol. 31 The following modifications were made: native Escherichia coli L-asparaginase was administered at a dose of 10 000 U/m 2 either as a deep intramuscular (IM) injection or as an IV infusion. During the protocol M phase, highdose methotrexate (HDMTx) was administered at a dose of 3 g/m 2 along with leucovorin rescue.…”
Section: Chemotherapymentioning
confidence: 99%
“…Patients were administered a modified Berlin-Frankfurt-M ünster 90 (BFM-90) protocol. 31 The following modifications were made: native Escherichia coli L-asparaginase was administered at a dose of 10 000 U/m 2 either as a deep intramuscular (IM) injection or as an IV infusion. During the protocol M phase, highdose methotrexate (HDMTx) was administered at a dose of 3 g/m 2 along with leucovorin rescue.…”
Section: Chemotherapymentioning
confidence: 99%
“…[1][2][3][4] In the studies AIEOP-ALL 91 and ALL-BFM 90, it was shown that conventional induction therapy (5 weeks) followed by 9 chemotherapy blocks and maintenance therapy led to poor results (5-year event-free survival [EFS] of 40%) in high-risk (HR) patients (approximately 15% of the ALL population), including infants and children with Philadelphia-positive ALL. 5,6 In the subsequent AIEOP ALL 95 study, treatment strategy was based on conventional BFM therapy and intensified with 3 chemotherapy blocks and double-reinduction therapy and improved the V.C. and M.G.V.…”
Section: Introductionmentioning
confidence: 99%
“…The patients who were administered low-dose cranial irradiation developed head and neck tumours [9]. Cranial irradiation is used for both prophylaxis and treatment of CNS disease in ALL [3]. Early institution of adequate CNS therapy is critical for eliminating clinically evident CNS disease at diagnosis and for preventing CNS relapse in patients without clinical CNS involvement at diagnosis [4].…”
Section: Discussionmentioning
confidence: 99%
“…Patients at high risk of CNS relapse (e.g. presence of hyperleucocytosis or T-cell ALL) continue to require cranial radiation in addition to extended intrathecal chemotherapy but its role is controversial [3, 4]. Higher doses of radiation are associated with the development of a second neoplasm (many of which are benign or of low malignant potential) [5].…”
Section: Introductionmentioning
confidence: 99%